Cognitive Dysfunctions and Assessments in Multiple Sclerosis - Oreja-Guevara, Celia; Ayuso Blanco, Teresa; Brieva Ruiz, Luis; Hernández Pérez, Miguel Ángel; Meca-Lallana, Virginia; Ramió-Torrentà, Lluís (Frontiers in Neurology, 2019)
Cognitive impairment has been reported at all phases and all subtypes of multiple sclerosis. It remains a major cause of neurological disability in young and middle-aged adults suffering from the disease. The severity and type of cognitive impairment varies considerably among individuals and can be observed both in early and in later stages. The areas which have commonly shown more deficits are: information processing speed, complex attention, memory, and executive function. Even though an alteration in both the white matter and in the grey matter has been found in patients with multiple sclerosis and cognitive impairment, the underlying process still remains unknown. Standardized neurological examinations fail to detect emerging cognitive deficits and self-reported cognitive complaints by the patients can be confounded by other subjective symptoms. This review is a comprehensive and short update of the literature on cognitive dysfunctions, the possible confounders and the impact of quality of life in patients with multiple sclerosis.